PENDALAMAN MATERI AKUNTANSI AKTIVA TETAP BAGI SMA KRISTEN YUSUF JAKARTA - Sastrasasmita, Emillia; Lie, Angel; Thirza, Selvyna (Jurnal Serina Abdimas, 2024)
One strategy that needs to be outlined carefully is the efficiency and effectiveness of using company resources. Fixed assets are company resources that are important for use in the company's operational activities. In this PKM activity, the PKM implementer provides financial accounting training, especially related to fixed assets. The partner is Yusuf Christian School, which is in Jembatan Dua, North Jakarta. On the initial survey, the PKM team obtained information that the partner had not studied fixed assets material specifically and completely. This is because the accounting material taught according to the high school curriculum is limited to the accounting cycle in service companies and trading companies. Therefore, fixed assets are one of the topics that students find difficult when they want to take part in accounting competitions. Yusuf Christian High School recorded many winners in various accounting competitions held at both high school and university levels. To maintain this achievement, school principals always need additional training to increase the insight and readiness of their students. This PKM activity aims to provide understanding and guidance to partners regarding fixed assets, both during acquisition, depreciation and reporting in financial reports. This training activity was held on May 16, 2024, with a duration of 120 minutes. This activity will be published in a journal resulting from the seminar held by Tarumanagara University and additional output in the form of intellectual property rights. ABSTRAK Salah satu strategi yang perlu digariskan dengan cermat adalah efisiensi dan efektivitas pemakaian sumber daya milik perusahaan. Aktiva tetap adalah sumber daya perusahaan yang penting dimanfaatkan dalam kegiatan operasional perusahaan. Pada kegiatan PKM ini, pihak pelaksana PKM memberikan pelatihan akuntansi keuangan khususnya berkaitan dengan aktiva tetap. Pihak mitra adalah Sekolah Kristen Yusuf yang berlokasi di Jembatan Dua, Jakarta Utara. Berdasarkan survei awal, tim PKM memperoleh informasi bahwa pihak mitra belum mempelajari materi aktiva tetap secara khusus dan lengkap. Hal ini disebabkan materi akuntansi yang diajarkan menurut kurikulum SMA terbatas pada siklus akuntansi di perusahaan jasa dan perusahaan dagang. Oleh karenanya aktiva tetap merupakan salah satu topik yang menjadi kesulitan siswa-siswi saat hendak mengikuti lomba akuntansi. SMA Kristen Yusuf mencatat banyak mendapatkan juara di aneka lomba akuntansi yang diadakan baik di tingkat Sekolah Tinggi maupun Universitas. Untuk mempertahankan prestasi ini, maka Kepala sekolah senantiasa membutuhkan pelatihan tambah untuk menambah wawasan dan kesiapan dari siswa-siswinya. Kegiatan PKM ini bertujuan memberikan pemahaman dan pembinaan kepada mitra tentang aktiva tetap, baik saat perolehan, penyusutan maupun pelaporan di laporan keuangan. Aktivitas pelatihan ini diadakan pada tanggal 16 Mei 2024 dengan durasi waktu 120 menit. Kegiatan ini akan dipublikasikan pada jurnal hasil dari penyelenggaraan seminar oleh Universitas Tarumanagara dan luaran tambahan berupa hak kekayaan intelektual.